Estimation of the hydraulic width of the subcatchment depending on the degree of detail of the drainage system model - Nowogoński, Ireneusz; Ogiołda, Ewa; Musielak, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the current state of knowledge in the field of estimating preliminary values of storm water subcatchment calibration parameters in the case of using the Storm Water Management Model (SWMM) for building a model of storm water drainage system.
Keywords: drainage system; drainage; modelling; runoff; storm water; SWMM; system odwadniający; drenaż; modelowanie; spływ; woda deszczowa